Translational Studies on Anti-Atrial Fibrillatory Action of Oseltamivir by its in vivo and in vitro Electropharmacological Analyses - Kambayashi, Ryuichi; Izumi-Nakaseko, Hiroko; Goto, Ai; Tsurudome, Kazuya; Ohshiro, Hironori; Izumi, Taku; Hagiwara-Nagasawa, Mihoko; Chiba, Koki; Nishiyama, Ryota; Oyama, Satomi; Nunoi, Yoshio; Takei, Yoshinori; et al. (Frontiers in Pharmacology, 2021)
Oseltamivir has been shown to prolong the atrial conduction time and effective refractory period, and to suppress the onset of burst pacing-induced atrial fibrillation in vitro. To better predict its potential clinical benefit as an anti-atrial fibrillatory drug, we performed translational studies by assessing in vivo anti-atrial fibrillatory effect along with in vivo and in vitro electropharmacological analyses. Oseltamivir in intravenous doses of 3 (n=6) and 30 mg/kg (n=7) was administered in conscious state to the persistent atrial fibrillation model dogs to confirm its anti-atrial fibrillatory action. The model was prepared by tachypacing to the atria of chronic atrioventricular block dogs for >6 weeks. Next, oseltamivir in doses of 0.3, 3 and 30 mg/kg was intravenously administered to the halothane-anesthetized intact dogs to analyze its in vivo electrophysiological actions (n=4). Finally, its in vitro effects of 10-1,000 μM on IK,ACh, IKur, IKr, INa and ICaL were analyzed by using cell lines stably expressing Kir3.1/3.4, KV1.5, hERG, NaV1.5 or CaV1.2, respectively (n=3 for IK,ACh and IKr or n=6 for IKr, INa and ICaL). Oseltamivir in doses of 3 and 30 mg/kg terminated the atrial fibrillation in 1 out of 6 and in 6 out of 7 atrial fibrillation model dogs, respectively without inducing any lethal ventricular arrhythmia. Its 3 and 30 mg/kg delayed inter-atrial conduction in a frequency-dependent manner, whereas they prolonged atrial effective refractory period in a reverse frequency-dependent manner in the intact dogs. The current assay indicated that IC50 values for IK,ACh and IKr were 160 and 231 µM, respectively, but 1,000 µM inhibited INa, ICaL and IKur by 22, 19 and 13%, respectively. The extent of INa blockade was enhanced at faster beating rate and more depolarized resting membrane potential. Oseltamivir effectively terminated the persistent atrial fibrillation, which may be largely due to the prolongation of the atrial effective refractory period and inter-atrial conduction time induced by IK,ACh and IKr inhibitions along with INa suppression. Thus, oseltamivir can exert a powerful anti-atrial fibrillatory action through its ideal multi-channel blocking property; and oseltamivir would become a promising seed compound for developing efficacious and safe anti-atrial fibrillatory drugs.